High dose frusemide in the treatment of hypertension in chronic renal insufficiency and of terminal renal failure. (April 1971) - Rastogi, S. P.; Volans, G.; Elliott, R. W.; Eccleston, D. W.; Ashcroft, R.; Webster, D.; Kerr, D. N. S.
Abstract : Frusemide in doses up to 2000 mg per day orally has proved a useful adjuvant therapy for resistant hypertension in patients with chronic renal failure, A worth-while diuresis is uncommon if the creatinine clearance is below 2 ml per minute but a useful, though often temporary, effect is obtained in the range 2 to 4 ml/min. Above this level of renal function the extent of the diuresis is not reliably predictable from the creatinine clearance but must be found individually for each patient. The dose should be increased with particular caution in patients with chronic pyelonephritis and a creatinine clearance above 10 ml per minute. Side-effects, other than those of excessive diuresis, have been uncommon. Hypokalaemia is readily prevented by the administration of potassium supplements and spironolactone. A rise in plasma urate is common but not usually dramatic and it has not precipitated secondary gout in our experience to date.